PERAN FILSAFAT BAGI PENGEMBANGAN DAERAH DAN PENINGKATAN SEMANGAT KEBANGSAAN - Kaelan Kaelan (Jurnal Filsafat "WISDOM", 2007)
As we have seen in its fact, the reformation program which is implemented not on the base of the Indonesian nation’s core philosophy drags Indonesian to come into multi-crisis situation. The violence conflict, terrorism, ethnical, racial, class and religious conflicts in this country had sacrificed a big amount of innocence nation’s generation. All of that is caused by unemployed philosophical base of Indonesian state, Pancasila which is dealt with divinity values, humanity, nationality, democracy and social justice in the process of reformation. Therefore, to form the democratic, religious and civilized society in the process of reformation since globalization era, the revitalization of nation state’s philosophical foundation is a must. In addition to form such society, the bureaucrats and political elites ought to develop their political communication attitude based on the morality, religious and civilized values as its result as to realize the welfare society on the togetherness as its foundation. In accordance with both national and rural developments, the philosophy of nation-state must be despised as the foundation of paradigmatic orientation of culture strategy because of national and rural developments are complex problem. Philosophy provides an inter-connected policy foundations and guidance in finding a wise solution to the complex problem.